Tess Hofmann, Matthias Bjørnlund, Vasileios Meichanetsidis (eds), The Genocide of the Ottoman Greeks: Studies on the State-sponsored Campaign of Extermination of the Christians of Asia Minor (1912-1922) and its Aftermath: History, Law, Memory - Kitroeff, Alexander (The Historical Review/La Revue Historique, 2014)
No abstract